Changes of bird behavior in response to magnetic fields anomaly before the earthquake: a review - Muhyiatul Fadilah; Riandi Riandi; Anna Permanasari; Enok Maryani (UNIVERSITAS NEGERI PADANG, 2020)
Animal behavior is a response to external environmental conditions through detection by certain senses. Changes in physical factors in the environment before the earthquake (magnetic field anomaly) also influence the expression of specific behavioral changes in birds, namely the flight activity. However, scientific explanation of changes in orientation or direction of flight before the earthquake was not yet available. This article aims to describe the mechanism of bird's biological response to changes in the magnetic field before the earthquake. This study is a literature review. The results of theoretical synthesis explain that birds use magnetic receptors and light receptors that recognize changes in the magnetic field before the earthquake followed by an increase in the amount of intracellular calcium ions. Abnormal amounts of calcium stimulate the formation of more ATP which activates the function of actin and myosin, therefore muscle cells experience a bathmotrope effect expressed in the form of changes in flight direction.